Distributed Cognition in Victorian Culture and Modernism - Anderson, Miranda (The Edinburgh History of Distributed Cognition : EHDC, 2022)
Reinvigorates our understanding of Victorian and modernist works and societyOffers a wide-ranging application of theories of distributed cognition to Victorian culture and ModernismExplores the distinctive nature and expression of notions of distributed cognition in Victorian culture and Modernism and considers their relation to current notionsReinvigorates our understanding of Western European works - including Wordsworth, T. S.